Parent-of-origin effects in MS: observations from avuncular pairs. - Herrera, B; Ramagopalan, S; Lincoln, MR; Orton, S; Chao, M; Sadovnick, A; Ebers, G (2008)
BACKGROUND: Multiple sclerosis (MS) is a complex neurologic disease of unknown etiology and inheritance pattern, but with increasing incidence among females. The study of aunt/uncle-niece/nephew (AUNN) pairs has potential to shed light on the on complex trait inheritance as this group can be divided into eight different pair types by gender, MS status, and parent of origin. METHODS: Using a cohort of 807 avuncular MS families with 938 affected AUNN pairs ascertained from a longitudinal, population-based Canadian database, we examined differential MS transmission by separating affected pairs into likely maternal and paternal trait origin. RESULTS: We observed an increased number of avuncular pairs connected through unaffected mothers compared to unaffected fathers (p = 0.008). To restrict confounders introduced by families with multiple pairs the overall number of maternal and paternal families were compared, to reveal a significantly higher number of maternal families (p = 0.038). Female-to-male sex ratios were higher among affected nieces/nephews when compared to the sex ratio for aunts/uncles (0.00042). CONCLUSIONS: This observation independently confirms previous findings of a "maternal parent-of-origin" effect in multiple sclerosis (MS) susceptibility. These findings highlight the special contribution that can be derived from avuncular pairs. These underutilized pairings can compare transmission by the gender of affected aunt-uncle, the unaffected transmitting parent, and by that of the affected offspring. This strategy may be especially profitable in diseases where parent-of-origin effects are being sought. These findings also independently confirm the increasing rate of MS in females, demonstrating that familial cases are influenced by the same environmental factors as the general MS population.